(De) regulation of working time, employer capture, and 'forced availability': a comparison between the UK and Cyprus food retail sector. Issue 21 (30th November 2017) - Hadjisolomou, Anastasios; Newsome, Kirsty; Cunningham, Ian
Abstract: This article is concerned with exploring how working time is regulated and experienced in the international food retail sector in the UK and Cyprus. Following Martinez-Lucio and Mackenzie the article accepts that regulation in employment relations is a multifaceted phenomenon shared by a number of competing actors at different institutional levels. The paper highlights the limitations of working time regulation in the two countries and argues that employers are increasing their control over the timing and allocation of shifts and working time. The paper illustrates how employers 'capture' working time regulation by exercising their prerogative to more closely match working time with the exigencies of customer demand. In this environment, the paper reveals how employees are experiencing practices such as 'forced availability', coupled with pressure to extend working hours as well as facing increasing levels of unpredictability as to when they are required to attend work.